Land Resources of Russia -- Maps of Permafrost and Ground Ice, Version 1 - National Snow and Ice Data Center (National Snow and Ice Data Center (NSIDC))
This data set includes maps of permafrost extent, permafrost temperature, the permafrost boundary, and ground ice thickness for all of Russia. The maps are ESRI Shapefiles, which were digitized from paper maps taken from the World Atlas of Snow and Ice Resources, 1997, Institute of Geography, Russian Academy of Sciences, Moscow, Russia. The scale of the source maps range from 1:20, 000, 000 to 1:40, 000, 000. Polygons were assigned attributes based on the classes used in the legends of the paper map. These data were extracted from a larger collection entitled Land Resources of Russia. Data and documentation © 2002 copyright International Institute for Applied Systems Analysis and the Russian Academy of Sciences.